Comprehensive evaluation of characteristics of left ventricular myocardium in a subject with non-coronary arterial cardiac dysfunction through segment by segment analysis using various diagnostic modalities - Ono, Hisako; Funabashi, Nobusada; Uehara, Masae; Yajima, Rei; Kataoka, Akihisa; Ueda, Marehiko; Miyauchi, Hideyuki; Daimon, Michiko; Takaoka, Hiroyuki; Komuro, Issei (International journal of cardiology, 2010)
We performed segment by segment analysis for comprehensive evaluation of the characteristics of the left ventricular (LV) myocardium by multislice CT (MSCT), magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT) and positron emission tomography (PET) in a patient with non-coronary arterial cardiac dysfunction. If diagnosis had been performed only by transthoracic echocardiogram and conventional coronary angiography, this subject might have been diagnosed as having dilated cardiomyopathy. However, we succeeded in the detailed evaluation of characteristics of LV myocardium non-invasively. Because of the difference in spatial resolution, MSCT and MRI could only detect focal fibrosis and MSCT could only detect fatty changes in the LV myocardium with an accurate ratio of thickness of lesions in comparison with the thickness of the whole LV myocardium. Conversely, a drawback of PET and SPECT was the partial volume effect and these methods could visualize the lesions as only diffuse decrements of attenuation and could not provide detailed information. Furthermore in MSCT, LV wall motion abnormality could be visualized by showing the ribs, sternum and descending aorta and in particular MSCT could obtain much information, including extra cardiac findings.